2021
DOI: 10.3390/jcm10194607
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride and Small Dense LDL-Cholesterol in Patients with Acute Coronary Syndrome

Abstract: Background: Small dense LDL-cholesterol is an established risk factor for atherosclerosis but is not routinely measured in daily practice. The association between small dense LDL-cholesterol and triglyceride, which in turn is routinely measured, in patients with acute coronary syndrome remains unknown. Methods: Consecutive patients with acute coronary syndrome who were admitted to our institute were prospectively included, and serum samples were obtained on admission. The association between small dense LDL-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The number of small dense LDL-cholesterol particles may theoretically increase along with triglyceride levels, particularly when the level of LDL-cholesterol is high. In the clinical literature, there is a mild-to-moderate correlation between triglyceride levels and actual measured small dense LDL-cholesterol levels [18]. Thus, our finding that pemafibrate decreased small dense LDL-cholesterol levels along with triglyceride levels may not be surprising, although it had not been previously validated [19].…”
Section: Pemafibrate and Small Dense Ldl-cholesterolmentioning
confidence: 70%
See 1 more Smart Citation
“…The number of small dense LDL-cholesterol particles may theoretically increase along with triglyceride levels, particularly when the level of LDL-cholesterol is high. In the clinical literature, there is a mild-to-moderate correlation between triglyceride levels and actual measured small dense LDL-cholesterol levels [18]. Thus, our finding that pemafibrate decreased small dense LDL-cholesterol levels along with triglyceride levels may not be surprising, although it had not been previously validated [19].…”
Section: Pemafibrate and Small Dense Ldl-cholesterolmentioning
confidence: 70%
“…On the contrary, other variables are also associated with a higher burden of small dense LDL-cholesterol. For example, insulin resistance, which is often seen in patients with metabolic syndrome, can also increase the burden of small dense LDL-cholesterol [21], especially in patients with obesity [18]. A recent study found that pemafibrate improved insulin resistance and maintained beta-cell function, which were correlated with improvement in lipid abnormality [22].…”
Section: Pemafibrate and Small Dense Ldl-cholesterolmentioning
confidence: 99%